2005
DOI: 10.1177/1043659605274948
|View full text |Cite
|
Sign up to set email alerts
|

Culturally Competent Scholarship in Nursing Research

Abstract: Assignment of Meleis scores is feasible and useful for evaluating cultural competence of research reports.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…The incorporation of such culturally responsive research practices with language minorities has the potential to enhance trust and, thus, improve the recruitment and retention of language minorities. In addition, the inclusion of culturally responsive criteria throughout the research process may generate results with improved validity (Jacobson et al, 2005) and, thus, further the knowledge base regarding language minorities. More important, the advancement of research with language minorities is an important step toward the improvement of health and social services access and quality of care among this group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of such culturally responsive research practices with language minorities has the potential to enhance trust and, thus, improve the recruitment and retention of language minorities. In addition, the inclusion of culturally responsive criteria throughout the research process may generate results with improved validity (Jacobson et al, 2005) and, thus, further the knowledge base regarding language minorities. More important, the advancement of research with language minorities is an important step toward the improvement of health and social services access and quality of care among this group.…”
Section: Resultsmentioning
confidence: 99%
“…To our knowledge, Meleis's framework (1996) is one of the few that has integrated the concept of cultural competence into research methods. The framework has been used to evaluate culturally competent knowledge development (Mendias & Guevara, 2001), culturally specific measurements (Im, Meleis, & Lee, 1999), and the evaluation of the rigor and credibility of research with diverse populations (Jacobson, Chu, Pascucci, & Gaskins, 2005;Mill & Ogilvie, 2003;Saltus, 2006). Although Meleis developed these criteria for nursing scholars, we believe them to be valid for culturally competent social work research because they focus on values relevant to social work practice, such as awareness of power differences and empowerment perspectives.…”
mentioning
confidence: 99%
“…Providers need to learn more about folk care practices, including voodoo, to determine what is being used to treat the current illness, and plan care accordingly to include these practices. Jacobson, Chu, Pascucci and Gaskins (2005), report that cultural competence requires willingness and skills to adapt and negotiate policies and procedures to the mutual satisfaction of the health professional and the care recipient. Yurkovich, Clairmont & Grandbois (2002) concur that cultural responsiveness requires a person to create culturally congruent care through collaboration with clients.…”
Section: )mentioning
confidence: 99%
“…Jacobson et al (2005) suggested agreement in the nursing literature that cultural competence is multidimensional. It is learned and incorporates self-awareness through which judgments about cultural differences are filtered.…”
mentioning
confidence: 94%